The effects of economic growth, trade liberalization, and financial development on environmental sustainability in West Africa. The role of institutions - Franklin Bedakiyiba Baajike; Enoch Ntsiful; Angela Boakye Afriyie; Eric Fosu Oteng-Abayie (Research in Globalization, 2022)
This study looks at how economic growth, trade liberalisation, and financial development affect the health of the environment in West Africa. The study also looks at how efficient institutions help make the environment in the ECOWAS region more stable. Therefore, the study tested the validity of the Environmental Kuznets Curve (EKC) hypothesis in the sub-region. The study employs the system generalised method of moments (system-GMM) estimation technique for 2005–2018. Other estimation techniques, including the pooled ordinary least squares (POLS), the fixed effect, the random effect and the difference generalised method of moments (d-GMM), are also used for robustness checks. The empirical results reveal that the initial stages of economic growth adversely affect environmental sustainability but improve it after a certain level. The Environmental Kuznets Curve (EKC) hypothesis is thus validated for the ECOWAS sub-region. The results also showed that trade liberalisation hurts environmental sustainability but moves towards environmental sustainability in the presence of quality institutions and a well-regulated market. The results imply that policy considers the quality of institutions and improvements in the financial sector to preserve the environment and limit erratic climate change. Data availability was the main challenge that we encountered during this study. This limited the scope of the study in terms of the sample size. The implication is that our findings does not take into account the changes in the variables for periods before 2005. This study is the first to comprehensively analyse environmental sustainability in the perspective of the entire West Africa sub-region. The recommendations from this study are therefore exclusive to all countries within the sub-region.